On the problem of optimal structure design subjected to regular lifetime criterion - Pho, Nguyen Van (Vietnam Journal of Mechanics, 1995)
The objective function of problem of optimal structure design can be chosen differently. For example the objective function can be the weight, the net cost, the regular resistance, the regular reliability, an so on. In this paper the problem of optimal structure design, subjected to regular lifetime condition for all elements is considered. The author sets up the problem, proposes an iterative method for solving and apply the obtained results to a simple example.